The Effect of Differentiated Learning on Understanding the Concept of Quadratic Functions at MAN 2 Palu City - Khairil Anwar; Rafiq Badjeber; Yulia Yulia (Journal of Educational Sciences, 2026)
Students’ understanding of mathematical concepts, particularly in quadratic functions, is still relatively low because the material requires abstract and representational thinking skills. Therefore, an adaptive learning approach that accommodates students’ learning characteristics is needed. This study aimed to determine the effect of differentiated instruction on students’ understanding of quadratic function concepts in class X of MAN 2 Palu City. This study employed a quantitative approach with a quasi-experimental method using a One-Group Pretest-Posttest Design. The research sample was selected through purposive sampling. The research instrument consisted of an essay test on quadratic function conceptual understanding that had been validated by experts. Data were analyzed using descriptive statistics and inferential statistics through the Paired Sample t-Test. The results showed that the average pretest score of students was 77.17, while the average posttest score increased to 88.17 after the implementation of differentiated instruction. The hypothesis testing results indicated a significance value of less than 0.05, showing a significant difference between pretest and posttest scores. In addition, the Cohen’s d effect size indicated a very large effect category. Thus, differentiated instruction can be considered an effective learning approach to improve students’ understanding of quadratic function concepts.